2013
DOI: 10.1093/aje/kws391
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bisphenol A and Obesity in US Children

Abstract: Childhood obesity, a major public health problem, can lead to cardiovascular disease in adulthood. Studies have implicated exposure to bisphenol A (BPA), a commonly used chemical, in the development of obesity in adults. However, literature is limited on this association in children. We examined the association between urinary BPA and obesity in children aged 6-18 years from the National Health and Nutrition Examination Survey (2003-2008). The primary exposure was urinary BPA and the outcome was obesity, defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
92
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(101 citation statements)
references
References 41 publications
7
92
0
2
Order By: Relevance
“…These findings are consistent with other large-scale cross-sectional studies of adults in the USA 11,12 and China, 13 as well as with studies in children. [30][31][32][33] Effect sizes in our study were slightly lower than those reported using the US National Health and Nutrition Examination Survey 11 (OR [quartile 4 vs. 1] = 1.76) and were more similar with the study in Chinese adults 13 (OR [quartile 4 vs. 1] = 1.50). A possible explanation for the weaker associations, compared to US results, may be related to the substantially lower BPA concentrations in our study and the Chinese study.…”
Section: Discussionsupporting
confidence: 56%
“…These findings are consistent with other large-scale cross-sectional studies of adults in the USA 11,12 and China, 13 as well as with studies in children. [30][31][32][33] Effect sizes in our study were slightly lower than those reported using the US National Health and Nutrition Examination Survey 11 (OR [quartile 4 vs. 1] = 1.76) and were more similar with the study in Chinese adults 13 (OR [quartile 4 vs. 1] = 1.50). A possible explanation for the weaker associations, compared to US results, may be related to the substantially lower BPA concentrations in our study and the Chinese study.…”
Section: Discussionsupporting
confidence: 56%
“…6 Another study using the NHANES data reported that non-Hispanic white boys were more likely to be overweight/obese, independent of other major risk factors, as a result of exposure to BPA. 144 To support these associations, more research is needed using longitudinal studies to confirm the findings observed in the available cross-sectional studies. 6,[142][143][144] Phthalates are a group of man-made chemicals widely used in industrial and consumer product applications.…”
Section: Metalsmentioning
confidence: 96%
“…144 To support these associations, more research is needed using longitudinal studies to confirm the findings observed in the available cross-sectional studies. 6,[142][143][144] Phthalates are a group of man-made chemicals widely used in industrial and consumer product applications. 8,145,146 Exposure to phthalates can occur from food sources, plastic containers, flooring materials and wall coverings, medical devices, personal care products, lacquers, varnishes, and coatings.…”
Section: Metalsmentioning
confidence: 96%
“…The molecular effects by which BPA exerts its disrupting effects in adipose tissue during childhood are currently stimulating great interest in the scientific community (Bhandari et al 2013, Eng et al 2013, Harley et al 2013). Most of the published studies analyze the effects of BPA on adipogenesis in murine 3T3-L1 cells or in human cell cultures obtained from adult adipose tissue (Masuno et al 2005, Hugo et al 2008, Valentino et al 2013.…”
Section: Discussionmentioning
confidence: 99%